The setting of fenological- stadium of plum (Prunus domestica) varieties in 2012 - Czinege, Anikó (Acta Agraria Debreceniensis, 2013)
We planted experimental trees, namely 6 plum varieties grafted on 6 plum rootstocks in the spring of 2010. Our aim was to observe differences in the fenological-stages of plum rootstock and variety combinations. ‘Cacanska lepotica’, ‘Jojo’, ‘Katinka’, ‘Topfive’, ‘Topper’, ‘Toptaste’ plum varieties were planted on ‘Mirobalan’ (Prunus ceresifera var. ceresifera cv. myrabolan); damson (Prunus institicia) – ‘St Julien A’, ‘St Julien GF655/2’; and ‘Wawit’; ‘Wangwnheim’; ‘Fereley’ rootstocks. We observed the bud burst, the flowering course: at the start of the flowering, during the main flowering, and at the end of flowerings and the ripening of the plum. Finally we observed the difference in leaves falling observed in the case of the different varieties and rootstock combinations. The bursting of buds started with ‘Cacanska lepotica’, in March 16 and finished with ‘Jojo’ / ‘Mirobalan’ combination, in March 22. The starting of flowering course was in March 29 with ‘Topper’ / ‘St Julien GF655/2’ combinations and the end of flowering course finished with ‘Toptaste’ varieties, in April 3–4. The start of ripening of the plum was with ‘Katinka’ / ‘St Julien A’ combinations, in July 17. and the end of ripening of the plum finished with ‘Topper’ variety. The start of leaves falling began with ‘Cacanska lepotica’, in Sept 5–8 depending on irrigation, and ‘Katinka’, ‘Jojo’ varieties finished, in November 28–29.